2013
DOI: 10.1002/adma.201304120
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Assembly of Single‐Layered MoS2

Abstract: Assembly of single layers: Three-dimensional assembly of single-layered MoS2 is achieved on a large scale via a solution method. The as-prepared tubular architectures have tunable size and mesopores in the shell, which are desirable for applications. As a example, they exhibit excellent lithium storage properties and are highly active for hydrodesulfurization of thiophene resulting from their structural advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
326
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(339 citation statements)
references
References 50 publications
13
326
0
Order By: Relevance
“…It has been previously shown that the restacked thick MoS 2 layers during the cycling can indeed inhibit the conversion reaction via the reduced ion transport. 34 In fact, the same phenomenon was reported in a range of other dichalcogenide anode materials, where the peaks associated with the conversion reactions disappeared after the first cycle. 1 In the present case, however, the direct integration of MoS 2 nano-leaves on the VGNS backbone can provide a multiscale 3D interconnected structure with facile electronic and ionic conductivity, which may significantly promote the conversion reaction and enhance the specific capacity of lithium storage.…”
Section: Mos 2 /Vgns Libs and Her Y Wang Et Almentioning
confidence: 49%
“…It has been previously shown that the restacked thick MoS 2 layers during the cycling can indeed inhibit the conversion reaction via the reduced ion transport. 34 In fact, the same phenomenon was reported in a range of other dichalcogenide anode materials, where the peaks associated with the conversion reactions disappeared after the first cycle. 1 In the present case, however, the direct integration of MoS 2 nano-leaves on the VGNS backbone can provide a multiscale 3D interconnected structure with facile electronic and ionic conductivity, which may significantly promote the conversion reaction and enhance the specific capacity of lithium storage.…”
Section: Mos 2 /Vgns Libs and Her Y Wang Et Almentioning
confidence: 49%
“…The increasing specifi c capacity with cycling is common for various nanostructured metal oxide/sulfi de electrodes and could be attributed to the growth of the gel-like polymeric layer and possibly electrochemical activation of hybrid composites. [31][32][33][34][35][36] It is worth mentioning that the capacity and cyclic capacity retention results of the MoS 2 @CMK-3 composite are attractive compared to MoS 2 fl akes synthesized without CMK-3 ( Figure S4, see Supporting Information) and most previously reported MoS 2 -based nanostructures, [14][15][16][17][18][19]29,[37][38][39][40] as well as pure CMK-3 ( Figure S5, see Supporting Information). In addition, exept for the fi rst several cycles, the Coulombic effi ciency of the MoS 2 @CMK-3 electrode is nearly 100% during the entire charge-discharge cycling test.…”
Section: Doi: 101002/aenm201400902mentioning
confidence: 94%
“…[28][29][30] Thus, constructing three-dimensional (3D) MoS 2 heterostructures with suitable layers for catalytic applications is a reasonable approach. 28,31,32 However, controlling the synthesis of MoS 2 nanosheets as a cocatalyst remains a serious challenge, and most of the available 3D heterostructures are prepared by two or more steps. 17,28,33,34 Hence, developing a simple, controllable general approach to synthesize 3D MoS 2 -based heterostructures is of considerable interest for cocatalyst applications.…”
Section: Introductionmentioning
confidence: 99%